2004
DOI: 10.1590/s0101-81752004000200035
|View full text |Cite
|
Sign up to set email alerts
|

The availability of Piperaceae and the search for this resource by Carollia perspicillata (Linnaeus) (Chiroptera, Phyllostomidae, Carolliinae) in Parque Municipal Arthur Thomas, Londrina, Paraná, Brazil

Abstract: ABSTRACT. A study about the species of Piperaceae that are consumed by a colony of Carollia perspicillata (Linnaeus, 1758) in Parque Municipal Arthur Thomas (82,72 ha) was carried out. Five available species of Piperaceae were found in the park: Piper aduncum Linnaeus, Piper amalago (Jacq.) Yuncker, Piper crassinervium H.B.K., Piper gaudichaudianum Kunth and Piper sp. C. perspicillata fed on all of these species. During the spring, the most abundant item was P. amalago, but the consumption of P. aduncum was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
1
11
0
3
Order By: Relevance
“…This fact corroborates results in other studies that determined the nutrient amounts of fruits in the diet of frugivorous bats (Dumont et al, 2004;Lima and Reis, 2004;Oliveira et al, 2012). In the case of A. lituratus, analyses of fruits whose seeds were not found in the faeces were included, although they were commonly ingested by the species, according to the literature (Muller and Reis, 1992;Passos and Passamani, 2003;Mello et al, 2011), and which occur in the SPMG.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This fact corroborates results in other studies that determined the nutrient amounts of fruits in the diet of frugivorous bats (Dumont et al, 2004;Lima and Reis, 2004;Oliveira et al, 2012). In the case of A. lituratus, analyses of fruits whose seeds were not found in the faeces were included, although they were commonly ingested by the species, according to the literature (Muller and Reis, 1992;Passos and Passamani, 2003;Mello et al, 2011), and which occur in the SPMG.…”
Section: Discussionsupporting
confidence: 92%
“…Wendeln et al (2000) evaluated the nutrient composition of 14 species of Ficus in Panama, often selected by many frugivorous, including bats, and concluded that the genus could provide carbohydrates, lipids, proteins and minerals in the necessary amounts for sustain frugivorous only when combined different species within this genus. Lima and Reis (2004) calculated the nutrition composition of five Piper species consumed by C. perspicillata and reported higher carbohydrate when compared to lipid and protein values. Similar quantities were reported by Oliveira et al (2012), who determined the nutrient composition, including water, sugars and proteins, of seven genera and nine species of fruits consumed by bats of the Brazilian Pantanal.…”
Section: Introductionmentioning
confidence: 99%
“…There are different explanations concerning the occurrence of frugivorous bats in the Neotropics. In most cases, bat occurrence is associated with food distribution and availability (Morrison 1978;Heithaus & Fleming 1978;Fleming 1988;Lima & Reis 2004). In total, the neotropical savannah of Cerrado comprises about 106 bat species (Aguiar & Machado 2010) making it the richest group of mammals in this domain (Marinho-Filho & Guimarães 2001).…”
Section: Introductionmentioning
confidence: 99%
“…As plantas dos gêneros Cecropia e Piper costumam disponibilizar frutos em pequenas quantidades e por um período maior, prolongando o fornecimento de recursos ao longo do ano (LOBOVA et al, 2003;LIMA & REIS, 2004;FABIÁN et al, 2008 Os frutos consumidos por morcegos geralmente apresentam elevada concentração de água e açúcares, enquanto lipídeos e proteínas são encontrados em menor quantidade (MORRISON, 1980;WENDEIN et al, 2000). Vericamos que houve grande variação entre o peso fresco e peso seco das espécies analisadas (Tabela 1), em muitas espécies, o peso fresco é mais de quatro vezes maior do que o peso seco, como é o caso de T. formosa, C. uiti (maduro), F. luschnathiana e C. pachystachya.…”
Section: Resultsunclassified